Quality Assurance in the Open University Service Online Learning Tutorial - Niku, Elpipres Muhammad; Wiyono, Bambang Budi; Nurul Ulfatin; Maisyaaroh (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
Higher Education Quality Assurance as disseminated to tertiary institutions in Indonesia until 2007. This dissemination aims to make every university realize that the responsibility for the quality of higher education implementation in these tertiary institutions is no longer entirely in the hands of the Government, but especially in the hands of the universities themselves. . Apart from that, the dissemination also aims to inspire each university about what, why, who, where, when, and how to carry out quality assurance in higher education.